Mitigation of Coal Production Losses Due to Blockade Action through Holistic Community Development at PT Semesta Alam Barito Site - Dedy Waliyan (Indonesian Journal of Social Responsibility Review (IJSRR), 2025)
The action to stop operational activities of coal mining production at PT Semesta Alam Barito often occurred in 2023, resulting in the company's loss in the form of coal production loss. This incident is a picture of a less harmonious face between the company and the community around the mine. The company's presence and communication seem to lack synergy. This research was conducted to show good and correct practices regarding the Community Empowerment Program, which is one of the government's mandates in implementing GMP (Good Mining Practice) principles, implementing ESG (Environmental, Social, and Governance), implementing SDGs (Sustainable Development Goals), and also implementing the appeals of Murung Raya Regency government at Central Kalimantan. The research was conducted using descriptive quantitative and qualitative methods through literature review and direct observation in the field. The author applies improvement in the concept of the Community Empowerment Program and concludes optimistically that the right and competent personnel runs the Community Empowerment Program, carried out with a sincere heart, and implemented consistently and with full commitment, then portal activities that result in production loss can be suppressed, synergy of community with the company can be achieved, and an independent and developing community can be created.